AUDIT ENERGI LISTRIK PADA HOTEL SOTIS KUPANG - Evtaleny R Mauboy (Universitas Nusa Cendana, 2019)
Abstract— The Energy Audit is an assessment of energy consumption and the identification of energy savings, as well as recommendations to increase the efficiency of energy consumption and use of energy sources in the context of energy saving. This study aims to describe the testing of electrical energy in the rooms of the Sotis Kupang Hotel from the 2nd (second) to the 6th (sixth) floor, taking samples of 7 (seven) different room types and carried out a test of electrical energy in relation to the use of lamps and air conditioning. The method used in this study is data collection, survey, observation and direct measurement of the use of light and AC (air conditioning). The data analysis technique used is to determine the estimated value of the electrical energy consumption and the value of the energy consumption intensity (IKE). The calculation and analysis show the value of IKE is 30.96 kWh / m2/ year, which is categorized as